PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN MASYARAKAT TENTANG COVID-19 DI TANGERANG - Behaki, Muhamad Asep; Susilowati, Yuni; Winarni, Lastri Mei (Nusantara Hasana Berdikari, 2022)
Covid-19 has become a global public health problem. Lack of knowledge about COVID-19 has led to an increase in the number of positive COVID-19 patients. Health education is an action that is considered to increase knowledge and behavior of individuals or communities regarding COVID-19. Objective: The purpose of this study is to determine the effect of health education on the level of public knowledge about Covid-19. Research Design: quasi-experimental design (Pre and Post Test without control). Sampling technique: sampling in this study used a total sampling of 96 respondents with different levels of knowledge in Tangerang. Data Analysis: The data analysis in this study used univariate and bivariate analysis. Results: From the results of providing health education to 96 respondents, the results of the average pre-test and post-test with a P Value of 0.001 <0.05 so that H0 is rejected, it can be interpreted that health education has an influence on the level of public knowledge about COVID-19.